1998
DOI: 10.1182/blood.v92.12.4836.424k24_4836_4843
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Seven Low Incidence Blood Group Antigens Carried by Erythrocyte Band 3 Protein

Abstract: Recent studies have demonstrated that band 3 carries antigens of the Diego blood group system and have elucidated the molecular basis of several previously unassigned low incidence and high incidence antigens. Because the available serological data suggested that band 3 may carry additional low incidence blood group antigens, we screened band 3 genomic DNA encoding the membrane domain of band 3 for single-strand conformational polymorphisms. We found that the putative first ectoplasmic loop of band 3 carries b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…However, RBC alloantigenicity depends primarily on residues/modifications exposed to the extracellular milieu, regardless of their role in expression, localization, or function. Many blood group antigenic sites will not be subject to strong evolutionary pressure, as described previously for Diego and Kell . Biochemical differences in amino acid substitutions may also not be as critical for immunohematology, since several proven antigenic variations (Wu/DISK, KEL:‐22, KUCI‐, Co(b+), etc) result from amino acid substitutions that are considered “conservative.” Möller and colleagues filtered variants with extracellular localization for possible antigenicity, and Howe and Stack reported that meta‐SNP scores can be helpful.…”
Section: Discussionmentioning
confidence: 99%
“…However, RBC alloantigenicity depends primarily on residues/modifications exposed to the extracellular milieu, regardless of their role in expression, localization, or function. Many blood group antigenic sites will not be subject to strong evolutionary pressure, as described previously for Diego and Kell . Biochemical differences in amino acid substitutions may also not be as critical for immunohematology, since several proven antigenic variations (Wu/DISK, KEL:‐22, KUCI‐, Co(b+), etc) result from amino acid substitutions that are considered “conservative.” Möller and colleagues filtered variants with extracellular localization for possible antigenicity, and Howe and Stack reported that meta‐SNP scores can be helpful.…”
Section: Discussionmentioning
confidence: 99%
“…It is also believed that the Di a antigen takes part of an adhesion complex for malaria parasites ( Plasmodium sp .) on the surface of red blood cells, favoring human infection by these protozoa . Malaria by Plasmodium brasilianum has been reported in Brazilian Capuchin monkeys .…”
Section: Discussionmentioning
confidence: 99%
“…Characterization of a CCC→TCC mutation in exon 14 of SLC4A1 that gives rise to a Pro561Ser substitution in the third extracellular loop of band 3 defines BOW. Our results are concordant with those of Jarolim et al, 9 and, because of these independent findings, the ISBT Working Party has designated BOW as DI15 and rendered its previous designation (700.46) obsolete 6 . With respect to NFLD, SSCP analysis of SLC4A1 suggested that variation in both exons 12 and 14 might relate to NFLD expression.…”
Section: Discussionmentioning
confidence: 99%
“…Serologically, NFLD and BOW are well‐characterized 3,4 ; genetically, family studies have excluded NFLD from 10 of the established blood group systems and BOW from 5 of them. The recent expansion of the Diego blood group system 5,6 ; the sensitivity of NFLD and BOW to α‐chymotrypsin 3 ; the serologic relationship 7 among NFLD, BOW, and Wu (DI9) 8,9 ; and preliminary evidence 10 suggesting that NFLD might belong to the Diego blood group system prompted the current investigation.…”
mentioning
confidence: 99%
See 1 more Smart Citation